2018
DOI: 10.1016/j.bbadis.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The MELAS mutation m.3243A>G promotes reactivation of fetal cardiac genes and an epithelial-mesenchymal transition-like program via dysregulation of miRNAs

Abstract: The pathomechanisms underlying oxidative phosphorylation (OXPHOS) diseases are not well-understood, but they involve maladaptive changes in mitochondria-nucleus communication. Many studies on the mitochondria-nucleus cross-talk triggered by mitochondrial dysfunction have focused on the role played by regulatory proteins, while the participation of miRNAs remains poorly explored. MELAS (mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes) is mostly caused by mutation m.3243A>G in mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 95 publications
4
10
0
Order By: Relevance
“…As has been shown in human RPE samples attached to the choroidal neovascularization extracted by surgery, the EMT of the RPE is involved in AMD pathogenesis [ 17 ]. TGFβ, an inflammatory cytokine that induces EMT in the RPE [ 17 ], was upregulated in the MELAS iPSC-derived RPE, consistent with a previous report that showed augmented TGFB expression caused by the dysregulation of miRNAs in MELAS cybrids [ 58 ]. Mitochondrial dysfunction was reported to change intracellular Ca 2+ signaling and nuclear gene expression in an RPE cell line [ 59 ].…”
Section: Discussionsupporting
confidence: 87%
“…As has been shown in human RPE samples attached to the choroidal neovascularization extracted by surgery, the EMT of the RPE is involved in AMD pathogenesis [ 17 ]. TGFβ, an inflammatory cytokine that induces EMT in the RPE [ 17 ], was upregulated in the MELAS iPSC-derived RPE, consistent with a previous report that showed augmented TGFB expression caused by the dysregulation of miRNAs in MELAS cybrids [ 58 ]. Mitochondrial dysfunction was reported to change intracellular Ca 2+ signaling and nuclear gene expression in an RPE cell line [ 59 ].…”
Section: Discussionsupporting
confidence: 87%
“…Enhanced miR-218 levels also reduced the expression levels of the CRK, RHOA and PTPN1 genes involved in GBM progression [82][83][84]. Our results are supported by data in the literature indicating a decrease in the expression levels of PIK3CA [85], RHOA [86] and STAT3 [45,87] as a consequence of miR-218 overexpression.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with this a recent study analyzing the commonly associated MELAS mutation 3243A>G demonstrated that the mutation can promote increased transcription with development and EMT, through modulation of miRNA levels [96]. These results further support a mechanism by which alterations in the mtDNA can alter metastatic susceptibility and tumor progression.…”
Section: Mitochondrial Dna and Metastasissupporting
confidence: 77%